The Influence Of Corporate Governance Toward Firmâs Value And Probability Of Financial Distress: A Case In Indonesia Stock Exchange - Paramita, Adianti; Arifin, Zaenal (JOURNAL OF ECONOMIC SCIENCE, 2015)
The objective of this research is to measure the influence of corporate governance toward firmâs value and Probability of Financial Distress. The corporate governance practice is modeled by Corporate Governance Perception Index (CGPI) score which is issued by the Indonesian Institute for Corporate Governance (IICG). The firmâs values are assessed by Return on Assets (ROA), Return on Equity (ROE) and Tobinâs Q. Moreover, the probability of financial distress is modeled by Altman Z Score calculation. The analysis methods of this research use the regression model. The controlling variables of this research are companyâs size, leverage and growth. There are 108 sample of data that used in this study. The sample size is obtained from companies that are listed in CGPI and Indonesia Stock Exchange (IDX) during 2007 â 2012. The result from this study shows that good corporate governance practice has significantly influence companyâs Return on Assets, Return on Equity, and the probability of financial distress. Meanwhile, good corporate governance practice does not have any influence toward firm value.